2012
DOI: 10.1557/mrs.2012.232
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-barrier coatings for more efficient gas-turbine engines

Abstract: Gas-turbine engines used in transportation, energy, and defense sectors rely on high-temperature thermal-barrier coatings (TBCs) for improved effi ciencies and power. The promise of still higher effi ciencies and other benefi ts is driving TBCs research and development worldwide. An introduction to TBCs-complex, multi-layer evolving systems-is presented, where these fascinating systems touch on several known phenomena in materials science and engineering. Critical elements identifi ed as being important to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
553
0
24

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,217 publications
(577 citation statements)
references
References 49 publications
0
553
0
24
Order By: Relevance
“…Thermal barrier coatings (TBCs) have been widely employed to protect the hotsection components of gas turbines and accommodate the increase of turbine inlet temperature, resulting in the improvement of the generation efficiency [1][2][3][4]. Most of TBC systems are consisted of a superalloy substrate, an adhesive metallic bond coat, and a thermal insulating ceramic top coat.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal barrier coatings (TBCs) have been widely employed to protect the hotsection components of gas turbines and accommodate the increase of turbine inlet temperature, resulting in the improvement of the generation efficiency [1][2][3][4]. Most of TBC systems are consisted of a superalloy substrate, an adhesive metallic bond coat, and a thermal insulating ceramic top coat.…”
Section: Introductionmentioning
confidence: 99%
“…Os dois primeiros itens são extensivamente tratados na literatura, mas o menos discutido ou conhecido é o desenvolvimento dos Revestimentos para Barreira Térmica, mesmo considerando que seu uso na última década permitiu um aumento muito grande nas temperaturas das turbinas, muito maior que a possibilitada pelas mudanças na tecnologia de solidificação direcional e técnicas de obtenção de ligas de monocristal dos últimos 30 anos [7,8,9].…”
Section: Melhoramentos Tecnológicos Do Sistemaunclassified
“…Depois de alguns anos, foram aplicados os primeiros revestimentos do tipo MCrAlY, onde M se refere a Ni, Co ou Fe. Só bem posteriormente foram introduzidos os TBCs, revestimentos cerâmicos [9]. Existem, na atualidade, dezenas de patentes com variações do material MCrAlY original, largamente aplicados em revestimentos de engenharia na indústria aeroespacial e de turbinas de energia [4,10].…”
Section: Revestimentos Cerâmicosunclassified
See 1 more Smart Citation
“…With regard to processing, atmospheric plasma spraying (APS) is one of the most common techniques to produce these coatings due to its good balance between coating performance and low cost [2]. However in the last years the need of increasing the operational temperature of gas turbines has fueled an intense research activity to develop coatings systems with enhanced thermal insulation, in particular low thermal conductivity [3,4]. In this sense, in previous research it has been demonstrated that using fine (nano-or submicronstructured) instead of coarse (microstructured) powder as plasma feedstock gives rise to coatings with lower thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%